Beyond Quality at Entry : Portfolio Review on Gender Implementation of Agriculture Projects (FY08-13) - Mollard, Ingrid; Brearley, Emily; Vyzaki, Marialena; Taivalmaa, Sanna-Liisa (World Bank, Washington, DC, 2015)
The objective of this study was to go beyond a standard gender review of project design to increase knowledge of how and to what extent World Bank agriculture projects address gender issues during implementation. The study introduces a tool to track gender mainstreaming in the implementation phase of a project. The tool is then used to review the portfolio of current agriculture projects, establish a baseline, and suggest targets for gender mainstreaming for the future portfolio. There is a need to move beyond quality at entry to have a more realistic picture of gender mainstreaming in projects. The Agriculture Action Plan (2013-15) explicitly emphasizes the importance of reducing gender inequality in access to assets, services, collective action, and opportunities. The plan specifies key actions to increase the share of agriculture and rural development projects by 2015. That will (1) include gender analysis in its design, with a target of 100 percent, and (2) include gender mainstreaming in all three dimensions of design (analysis, actions, and ME), with a target of 75 percent. The reason for the 75 percent target is that gender analysis conducted at entry, for a relatively small set of projects, can reveal that gender specific actions and related ME are not needed. The focus on all three elements of design raises the bar for an agriculture project beyond the World Bank standard of satisfactorily addressing at least one of these elements. In addition, from FY15, all agriculture projects will be reviewed by the Gender team in the Agriculture Global Practice (GFADR) in terms of gender mainstreaming at concept note, preparation, and appraisal stages. This review indicates that a rating of gender Informed at entry is no guarantee that a project will successfully mainstream gender during implementation, although it is a good basis for success. In addition, this review shows that it is critical to track gender mainstreaming throughout the project cycle to identify gaps and opportunities in real time. Finally, the review shows that if a project neglects gender during the design phase, it can still catch up during implementation.